Reconstruction of the Amount of Certain Goods and Services Tax Rates for Traditional Health Services - Baharuddin Riqiey; Ahmad Rizal Roby Ananta; Sukardi; Istikhomah (Fakultas Hukum Universitas Airlangga, 2025)
The purpose of this study is to examine and analyze the authority of the Regency/City Regional Government in collecting and/or not collecting PBJT tax on entertainment services in the form of steam baths/spas and the reconstruction of the amount of PBJT rates for entertainment services in the form of steam baths/spas after the Constitutional Court Decision. The mention of steam baths/spas in this article must be interpreted as traditional health services as per the Constitutional Court Decision No. 19/PUU-XXII/2024. Therefore, this study is a legal study using three approaches, namely the statutory, conceptual, and case approaches. The results of this study indicate that the Regency/City Regional Government must collect PBJT on arts and entertainment services in the form of steam baths/spas as long as it is stated in the Regional Regulation. However, the Regency/City Government may not collect PBJT on arts and entertainment services in the form of steam baths/spas if there are or are met the requirements as stipulated in Article 6 paragraph (2) of Law No. 1 of 2022. Because the mention of steam baths/spas is stated to provide no guarantee of legal certainty and creates a negative stigma in society by the Constitutional Court, the logical consequence of this is to remove steam baths/spas from the category of discotheques, karaoke, nightclubs and bars and put them in the category of massage parlors and reflexology. So, the PBJT tariff for arts and entertainment services in the form of steam baths/spas is adjusted to Article 58 paragraph (1) of Law no. 1 of 2022 which levies the highest PBJT of 10%.